Teachers’ Perceptions of the Platforms Used for Assessing Learners’ Speaking Performance: Types, Benefits, and Challenges - Ira Putri Audina; Made Heri Santosa (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
In the teaching and learning process, one of the roles and responsibilities of teachers is to assess the skills and what is taught to students. In the assessment activity, the teacher can get feedback on the extent to which students understand what the teacher teaches. Even though the learning is done virtually, the assessment still has to be done. This study investigates teachers’ perceptions of the types, benefits, and challenges of platforms used to assess young learners’ speaking performance. The research data was obtained by conducting interviews with respondents through Google Meet and adopted the interview questions by Mpungose (2020) about the online assessment platforms. The researcher determined the respondents by using a purposive sampling technique where respondents used an online platform in assessing young learners’ speaking performance during distance learning. After the data was collected, the researcher analyzed it using an interactive model by Miles et al. (2014). This study indicates that there are various platforms that teachers can use to assess young learners’ speaking performance, including Zoom, Google Meet, Google Classroom, WhatsApp, and YouTube. The five platforms were revealed to be very useful to make it easier for teachers to assess learners’ speaking performance. Teachers can easily assess aspects of their pronunciation, fluency, grammar, and vocabulary through these five platforms. Besides helping assess learners’ speaking performance, this study also shows various challenges in its implementation, such as connection problems, assignment submission, and poor video and audio quality.